Public knowledge, attitudes, practices, and barriers to skin cancer screening in the United Arab Emirates. - Anan S Jarab; Walid Al-Qerem; Karem H Alzoubi; Mariam Al Mohammad; Shrouq R Abu Heshmeh; Yazid N Al Hamarneh; Tareq Mukattash; Maher Khdour (PLoS ONE)
Objective To assess knowledge, attitude, practice, and barriers to skin cancer screening among the general population of the United Arab Emirates (UAE). Methods In this cross-sectional study, an online-based questionnaire was distributed via online social media sites such as Facebook, WhatsApp, Twitter, and others to the residents of the UAE. The questionnaire evaluated socio-demographics, knowledge (8 items), attitudes (10 items), practices (14 items), and barriers (9 items) in the context of skin cancer screening. A binary logistic regression was conducted to assess variables associated with practice levels. Results The study included 924 participants (51.9% females), with a median (IQR) age of 32 (22-44) years. Results showed a window for knowledge improvement [median = 4 (3-6) out of a maximum potential score of 8], unfavourable attitudes [median = 37 (33-39) out of a maximum potential score of 50], inadequate practices [median = 41 (31-45) out of a maximum possible score of 70]. The most common barriers to skin cancer screening were lack of knowledge about skin cancer (74.1%), lack of awareness of the need for skin cancer screening (72.2%), and absence of symptoms (54.1%). Older age (OR = 0.985, 95%CI: 0.971-0.998) and lack of health insurance (OR = 0.478, 95%CI: 0.301-0.758) were associated with lower screening practices. Female gender (OR = 1.833, 95%CI: 1.361-2.469), being married (OR = 1.415, 95%CI: 1.006-1.992), being a non-smoker (OR = 1.568, 95%CI: 1.045-2.352) or a former smoker (OR = 2.555, 95% CI: 1.082-6.034), and more favourable attitudes (OR = 1.071, 95%CI: 1.044-1.096) were associated with higher screening practices. Conclusion The UAE population exhibited moderate knowledge, unfavourable attitudes, and inadequate practices regarding skin cancer screening, with several barriers identified. Targeted online and in-person awareness campaigns are crucial for improving public understanding and attitudes, thereby enhancing screening practices, especially among older adults, males, smokers, and those without health insurance.